Withametelin inhibits TGF-β induced Epithelial-to-Mesenchymal Transition and Programmed-Death Ligand-1 expression in vitro - Fathima, Ashna; Farboodniay Jahromi, Mohammad Ali; Begum, Sajeli A.; Jamma, Trinath (Frontiers in Oncology, 2024)
Withanolides are a group of naturally occurring plant-based small molecules known for their wide range of host cellular functions. The anticancer potential of withanolides has been explored in varying cancer cell lines in vitro. Based on our prior studies, among the tested withanolides, withametelin (WM) has shown significant cytotoxicity with the highest efficacy on HCT-116 colon cancer cells (IC50 0.719 ± 0.12µM). Treatment with WM reduced the TGF-β driven proliferation, colony-forming ability, migration, and invasiveness of HCT-116 cells in vitro. WM also downregulated the expression of mesenchymal markers such as N-CADHERIN, SNAIL, and SLUG in HCT-116 cells. At the molecular level, WM inhibited TGF-β induced phosphorylation of SMAD2/3 and reduced the expression of an immune checkpoint inhibitor programmed-death ligand-1 (PD-L1). Our study highlights the possible anticancer mechanisms of WM involving modulation of the TGF-β pathway and associated target gene expression, suggesting its potential utility in cancer therapy.